Limiar de detecção para gosto primário em idosos praticantes de atividade física - Abreu, Amanda Kelle Fernandes de (2014)
Older adults represent a segment of population that has more increased in recent years. In Brazil, estimates for next 20 years indicate that elderly population will exceed 30 million people, which can reach nearly 13% of population. Regular physical activity provides one of most opportunities for improving quality of life, improve physical condition and reduce disability and functional limitations of elderly people. The increasing of elderly population has raised need to understand changes that occur in this stage of life, as well as their implications, since, during aging, there are several physiological changes that can affect perception of food for older consumers. For these reasons, present study aimed to evaluate taste sensitivity in elderly people practitioners of physically active, since little is known about sensory responses provided by this group. Threshold test was used to determine detection threshold for salty and sweet flavors in 40 young adults (18-38 years), 40 elderly practitioners of regular physical activity (60-84 years) and 40 elderly no activity practitioners physical (60-87 years). Women accounted for 90% in the group of elderly practitioners of physical activity and 60% of non-elderly practitioners, feature explained by aging feminization process. Physically active elderly had 4.12 mMol thresholds for salty and 6.20 mMol for sweet taste, values close to the group of young adults surveyed and below values found in other studies that worked with sensory perception in the elderly. There were significant minimization of sensory changes of salty and sweet taste in elderly practitioners of physical activity, providing to this group sensorial perception capacity similar to young adults group. Physical activity contributes in some ways to the best development of sensorial perception of older people who practice physical activity, a positive factor for both active development of that group and to its perceptual capacity.